Leguminous green manure amendments improve maize yield by increasing N and P fertilizer use efficiency in yellow soil of the Yunnan-Guizhou Plateau - Gao, Xiaoye; He, Yan; Chen, Yu; Wang, Ming (Frontiers in Sustainable Food Systems, 2024)
The low utilization efficiencies of chemical N and P fertilizers largely threat the sustainability of agriculture. Green manure is conducive to increasing crop yield. This study aimed to explore the effects of leguminous and non-leguminous green manures on the maize production, and N and P fertilizers use efficiency. A green manure-maize rotation experiment was conducted in the Karst region of the Yunnan-Guizhou Plateau. The responses of maize yield, N (NUE) and P (PUE) fertilizer use efficiency to winter fallow fields treated with no fertilizer (CK) and traditional chemical fertilizers (WF), WF with alfalfa (AL), common vetch (CV) and oilseed rape (OR) green manures in 2020 and 2021. The results showed that compared with WF, the maize yield was significantly increased on average by 22% and 15% in AL and CV, respectively, while it was hardly affected in OR. AL significantly increased NUE and PUE by an average of 103% and 66%, and CV increased NUE by an average of 74% and 41%, respectively, while RA had no significant effects on PUE, and decreased NUE by 39% in the second year. Structural equation modeling (SEM) showed that green manures indirectly affected NUE and PUE due to soil available N and P, which directly and indirectly influenced maize N and P uptake, and then enhanced NUE and PUE. Linear regression results showed that maize production had positive relationships with NUE and PUE. Our findings highlight that non-legume green manure would hardly influence grain yield, while legume green manure could be effective for increasing maize production by increasing NUE and PUE, especially for alfalfa in yellow soil of the Yunnan-Guizhou Plateau.